1981
DOI: 10.1029/jb086ib11p10223
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene high‐silica rhyolites of the Coso Volcanic Field, Inyo County, California

Abstract: The high‐silica rhyolite domes and lava flows of the bimodal Pleistocene part of the Coso volcanic field provide an example of the early stages of evolution of a silicic magmatic system of substantial size and longevity. The rhyolites are sparsely porphyritic to virtually aphyric, containing qz + pl + san + bi + hb + mt ± allanite ± opx ± cpx ± fa ± il ± ap ± zircon phenocrysts. Major and trace element compositions of all 38 rhyolite extrusions are consistent with derivation from somewhat less silicic parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
2
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 36 publications
(12 reference statements)
4
78
2
1
Order By: Relevance
“…Manley and Bacon (2000) used the Al-in-hornblende barometer to show that mineral growth within the *0.6 to 0.3 Ma rhyolites imply that the depth to the top of the silicic magma body was *10 km (*270 MPa) and that by *0.04 Ma it had risen to *5.4 km (140 MPa). Following Bacon et al (1981), Mordick and Glazner (2006) concluded that Pleistocene basalts likely provided heat needed to generate Pleistocene rhyolite and may have been trapped beneath the Pleistocene rhyolite magma body, a possible explanation for why the Pleistocene basalts records greater depths than the Pliocene basalts.…”
Section: Geology Of Coso Volcanic Fieldmentioning
confidence: 99%
See 3 more Smart Citations
“…Manley and Bacon (2000) used the Al-in-hornblende barometer to show that mineral growth within the *0.6 to 0.3 Ma rhyolites imply that the depth to the top of the silicic magma body was *10 km (*270 MPa) and that by *0.04 Ma it had risen to *5.4 km (140 MPa). Following Bacon et al (1981), Mordick and Glazner (2006) concluded that Pleistocene basalts likely provided heat needed to generate Pleistocene rhyolite and may have been trapped beneath the Pleistocene rhyolite magma body, a possible explanation for why the Pleistocene basalts records greater depths than the Pliocene basalts.…”
Section: Geology Of Coso Volcanic Fieldmentioning
confidence: 99%
“…The dome names (numbers), their field relationships, and their major and trace element compositions used here to develop models for the petrogenetic and eruption history of the magma system come from Duffield et al (1980) and Bacon et al (1981). In general, Coso rhyolites are crystal-poor with the two oldest domes (38 and 28) and a third dome (5) located at the north end of the field being the exceptions.…”
Section: Description Of Rhyolites and Dated Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Pleistocene volcanic rocks consist of 38 separate domes and flows of high-silica rhyolite, and most of them are quite young; younger than 300,000 years. Bacon et al (1981) inferred from the rhyolite magma that there was a chemically stratified siliceous reservoir at depth. Most of the first production of the geothermal system was near Dome 53, which is near the Devil's Kitchen fumarolic area.…”
Section: Coso Geothermal Fieldmentioning
confidence: 99%